Agricultural biotechnology : country case studies : a decade of development - Persley, G. J.; MacIntyre, Reginald (Biotechnology in agriculture series, 2002)
Presents further material generated by the World Bank/ISNAR/Australian government biotechnology study. The volume covers the present status and future prospects for the application of biotechnology to solve agricultural and environmental problems in 12 countries.